Towards controlling intrinsic heat treatment of maraging steel during laser directed energy deposition. (August 2021) - Amirabdollahian, Sasan; Deirmina, Faraz; Harris, Luke; Siriki, Raveendra; Pellizzari, Massimo; Bosetti, Paolo; Molinari, Alberto
Abstract: The intrinsic heat treatment (IHT) during laser directed energy deposition (L-DED) of a maraging steel powder was investigated. The thermal history of each layer during the building process was simulated to evaluate the effect of the interlayer pause on the maximum and minimum temperatures experienced by the material. The minimum temperature decreases with the interlayer pause, enhancing the austenite to martensite transformation needed to trigger the intermetallic precipitation during the deposition of the subsequent layers. Specimens were then produced with different interlayer pauses, and the hardness profile, compressive strength, and the microstructure along the building direction were investigated and compared to the ageing curves. The results agree with the simulation and demonstrate that the intrinsic heat treatment may allow avoiding post-building heat treatment. Graphical abstract: Image, graphical abstract